Risk factors and sonographic endometrial thickness as predictors of tumour stage and histological subtype of endometrial cancer - Ivana Rizzuto; Rachel Nicholson; Wendy S. MacNab; Mythili Nalam; Rohit Sharma; Barnaby Rufford (Elsevier, 2019)
We evaluated the association between risk factors for endometrial cancer (EC) and sonographic endometrial thickness (ET) with FIGO stages at diagnosis. We also reported our experience in reliability of sonographic ET as screening tool for either histologic subtype I and II of EC. It was a case series study including 339 patients diagnosed with EC from 2010 to 2017 at the Ipswich Hospital, UK. Women with higher body mass index (BMI) presented at earlier stages when compared to women with lower BMIs (p-value = .046). By contrast, none of the variables: parity (p-value = .1630), use of HRT (p-value 0.7448), tamoxifen (p-value 0.0733) and diabetes (p-value = .1665) were statistically associated to FIGO stages. The mean of ET measurement was not statistically significant associated (p-value 0.0625) to stages. There was no statistic difference on mean ET at diagnosis between histologic subtypes I or II (p-value 0.804). According to our experience, BMI is associated to FIGO stage and endometrial sampling (ES) should be included in the working diagnosis of EC to obtain an early diagnosis in women with high BMIs even in premenopausal. Ultrasonographic measurement of the endometrium is equally reliable at determining cancer, but not at differentiating histologic subtypes I and II uterine cancers. However, ET does not correlate to FIGO stages at diagnosis. Keywords: Endometrial cancer, Risk factors, Endometrial thickness and FIGO stages